UTILIZATION OF DRY NOODLE WASTE AS SUBSTITUTION OF WHEAT FLOUR AGAINST GRWOTH AND FEED EFFICIENCY ON TILAPIA (Oreochromis niloticus) - Muchamad Nanafi Nurlaksana; Samsundari Sri; Anis Zubaidah (IJOTA (Indonesian Journal of Tropical Aquatic), 2023)
Fish was one of the result waters consumed by many Indonesians. Tilapia (Oreochromis nilaticu) is one of the freshwater fishery products that people in demand, tilapia has a delicious taste, One of the factors that affect the growth of cultivated fish is feed. The cost of feed can reached 60-70% of production cost component. This research was conducted at Fisheries Laboratory of Faculty of Agriculture - Animal Husbandry University of Muhammadiyah Malang. The method used in this research is an experimental method using Completely Randomized Design. In the study there were 5 treatments with the addition of different dry noodle flour that is 0%, 25%, 50%, 75% and 100% and one treatment of noodle control use flour whear, each treatment was repeated four times. The pellet feed is administered adlibitum for 40 days. The main parameters used include the Specific Growth Rate (SGR), Total Feed Consumption (JKP) and Feed Efficiency (EP) were then analyzed using ANAVA and continued with BNT testThe results showed that the effect of Pellet form feeding was very significant (**) on Specific Growth Rate (SGR) Calculate 11.102> from F.Table 5% (3.11) 1% (5,03), and Feed Efficiency EP) F. Calculate 20.752> from F.Table 5% (3.11) 1% (5,03). The quality of tilapia in this study ranged from 25-27 0C, dissolved oxygen ranged from 5.2 to 6.7 and the pH ranges from 6.7 to 8.1.The conclusion of this study P5 treatment of 100% dried noodle flour additions is the best feed with the highest SGR 1.54% and the lowest 0.81.Key Words: Pellet-Formed Feed, Specific Growth Rate (SGR), Total Feed Consumption (JKP,) and Feed Efficiency (EP) Tilapia.